PEMBELAJARAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN METODE EXAMPLE NON EXAMPLE PADA SISWA KELAS XI - Nenden Syarifah JM Listari; Tita Sri Handayani; Indra Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is in the background of the results of observations and evaluations that students do in writing, especially in writing explanatory texts by observing an image. Students still find it difficult to determine the structure of general statements, the sequence of cause and effect, and interpretation. The problem in this study is, how can the example non-example method be understood by students so that there are differences before and after using the method? Based on observations that have been made in class XI, students have difficulty writing the explanatory text. This study uses a pre-experimental method with a one group pre-test post-test design approach used by researchers by conducting an initial test before being given treatment so that it can be seen significantly the comparison of the values that have been carried out. The researcher took a sample of 30 students in class XI. Data sources obtained from students of class XI are in the form of initial test questions and final tests. Based on the results of the data that have been treated there are differences before using the Example Non Example method, namely the initial test (pretest) obtained an average value of 60 after using the Example Non Example method of the final test (posttest) of 80. So, it can be concluded that it has happened changes after being given learning by using the Example Non Example method in writing explanatory texts.